Student-Produced Video of Role-Plays on Topics in Cell Biology and Biochemistry: A Novel Undergraduate Group Work Exercise - Young, Paul William (Frontiers in Education, 2020)
Group role-plays are an excellent form of collaborative learning but are not widely used in the teaching of core scientific concepts at undergraduate level. I describe here an example of group role-plays being used to explore fundamental processes in cell biology, including vesicular trafficking, cell migration, cell division, endocytosis and the targeting of proteins to subcellular organelles. The students are cast in the roles of the key proteins involved in a particular process by the instructor, but groups are then given a free rein to develop a role-play that illustrates the process. The role-plays produced can be classified as analogy role-plays and choreographed or animated demonstrations. Videoing of the role-plays allows each group’s work to be shared with the class as a whole, with the videos proving useful as a revision aids leading up to the terminal exam. Templates for role-plays on eight core topics in cell biology and a model for peer input into the grading of individuals within groups are provided. The advantages of videoing the role-plays from both and instructor and student point of view are discussed. Student feedback supports the value of the role-play exercise in (1) encouraging scientific discussion, (2) promoting teamwork skills and self-awareness and (3) helping students, especially those visiting from abroad, to integrate with fellow classmates. These observations make the case that videoed role-plays, in which students play the roles of molecules, proteins, organelles or cell types, represent a potentially valuable form of collaborative learning in the cell and molecular life sciences.